Determination Of Debt Financial Behavior In Pandemic Covid-19 - Aprih Santoso; Sri Yuni Widowati; Nurhidayati Nurhidayati (Jurnal Riset Manajemen dan Bisnis, 2021)
This study examines the influence of attitudes, subjective norms and intentions on the behavior of taking credit for small entrepreneurs of Semarang city at the PANDEMI COVID 19. The population of this study includes all small entrepreneurs who take the Wibawa credit in the city of Semarang, amounting to 150 people. The number of samples is 60 people (based on the Slovin formula). The sample selection method is purposive sampling, with the following criteria: 1) small entrepreneurs taking credit for the first time. 2) small entrepreneurs already have families and still have dependents for school children.The analytical tools used are: validity test, reliability test, normality test, classic assumption test (multicolonierity test, heteroscedasticity test, multiple linear regression, hypothesis test (partial t-test and F test - Goodness of Fit test) and the coefficient of determination (R2 ). The results of this study indicate that financial literacy, subjective norms and intentions influence the financial behavior of small entrepreneurs in Semarang City at the PANDEMI COVID 19. The implication of this research is that implementing credit programs should not only focus on low interest rates, but also pay more attention to tenors. It is fitting for the involvement of non-government parties to be the focus of attention as another alternative in debt.